Factors determining the hatching success of Antarctic krill Euphausia superba embryo: lipid and fatty acid composition - Yoshida, T; Virtue, P; Kawaguchi, S; Nichols, PD (Marine Biology, 2011)
The present study addresses the effect ofmaternal diet on hatching success and condition of embryosand larvae of Antarctic krill Euphausia superba. Lipid andfatty acid content and composition were determined in fieldand laboratory samples. Developmental stages analyzed inembryos included: multiple-cell, gastrula, and limb-budstages. Larval stages analyzed included: nauplius I, naupliusII, and metanauplius. Laboratory-reared embryos werespawned by gravid females incubated under three feedinggroups: (1) phytoplankton mixture, (2) phytoplankton mixtureand minced clam, and (3) phytoplankton mixture,minced clam, and commercial larval food. Hatching successwas highest in group 3 (100%), lowest in group 1 (0%), andhighly variable in field samples (048%). Lipid decreasedslightly in embryos during embryonic development, whilelarge decreases in lipid were found during nauplius development.High levels of 18:2(n-6), 20:4(n-6), and 22:6(n-3)observed with group 3 samples coincided with high hatchingsuccess in krill embryos. The ratio of 22:6(n-3)/20:5(n-3)also correlated to hatching success of embryos. The fatty acidprofile of embryos in group 3 was similar to that of the fieldcollectedembryos, reflecting the contribution of the commerciallarval food in the maternal diet. In our study, thematernal diet was found to influence the fatty acid compositionof embryos and in turn affects the hatching success ofkrill. Specific polyunsaturated fatty acids appeared to playimportant roles in embryogenesis in krill.